2010
DOI: 10.1097/gme.0b013e3181b4c4ac
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of long-term treatment with raloxifene, a selective estrogen receptor modulator, on myocardial ischemia/reperfusion injury in ovariectomized rats

Abstract: Long-term treatment with RAL can reduce the severity of MI-induced arrhythmias and attenuate MI/R-induced damages and apoptosis in Ovx rats. This cardioprotective effect of RAL may be associated with inhibition of neutrophil infiltration and suppression of nuclear factor-kappaB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…The connection between the MPO level and cardiac parameter or tissue HO expression suggests a preventive role of estrogen therapy in cardiovascular pathological processes. Similarly to our results, Chung et al demonstrated that long-term treatment with RAL significantly decreased the cardiac activity of MPO in OVX rat [40]. While OVX increases the inflammation processes, the elevated levels of inflammatory markers can be decreased with hormone replacement therapy [41].…”
Section: Discussionsupporting
confidence: 89%
“…The connection between the MPO level and cardiac parameter or tissue HO expression suggests a preventive role of estrogen therapy in cardiovascular pathological processes. Similarly to our results, Chung et al demonstrated that long-term treatment with RAL significantly decreased the cardiac activity of MPO in OVX rat [40]. While OVX increases the inflammation processes, the elevated levels of inflammatory markers can be decreased with hormone replacement therapy [41].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, selective activation of ERβ provides cardioprotection that requires the availability of NO (Lin et al, 2009). Acute and chronic treatment of dogs or rodents with the SERM raloxifene also improves ischemia/reperfusion-related myocardial injury, and again partly involves NO-dependent mechanisms mediated by the PI 3 K/Akt-pathway (Chung et al, 2010; Nemcsik et al, 2004; Ogita et al, 2002; Ogita et al, 2004). A number of experimental studies on ischemia/reperfusion injury subsequently found beneficial effects mediated by both ERα and ERβ, yet some controversies exist whether both receptors provide acute and chronic cardioprotection (Deschamps et al, 2010).…”
Section: Protective Effects Of Gper On Myocardial Functionmentioning
confidence: 99%
“…The function of vascular endothelial cell is regulated by RAL via estrogen response elements or other pathways to protect vascular endothelial function [6]. RAL is expected to become a potential drug for the treatment of cardiovascular disease [7, 8]. …”
Section: Introductionmentioning
confidence: 99%